Multicultural Inclusive Education in the Deradicalization of Islamic Education in Indonesia - Fatoni, Fatoni; Susanto, Is; Pratama, Heri Okta; Julaihah, Siti (Universitas Islam Negeri Raden Intan Lampung, 2021)
It is projected that multicultural inclusive education will prevent acts of extremism and intolerance. This study aimed to examine how multicultural inclusive education could be used to deradicalize Islamic education in Indonesia. In June 2020, the researchers searched the Google Books database for library research. The prism technique was used to gather and extract data based on the established inclusion and exclusion criteria. According to the analysis, multicultural inclusive education can be employed as a substitute for instilling an understanding of peaceful coexistence in the contexts of nationality and humanity. If multicultural inclusive education is conducted properly by following the steps outlined, efforts to deradicalize Islamic education in Indonesia may be successful, as multicultural inclusive education is founded on consistency, openness, introduction, comprehension, recognition, and appreciation. This study illustrates that multicultural inclusive education can deradicalize Islamic education in Indonesia due to its adaptability to the primary material in Islamic education.